Comparison of Bispectral Index Monitor Data Between Standard Frontal-Temporal Position and Alternative Nasal Dorsum Position in the Intensive Care Unit: A Pilot Study. Issue 1 (9th February 2022) - Romito, Jia W.; Atem, Folefac D.; Manjunath, Anupama; Yang, Ailing; Romito, Bryan T.; Stutzman, Sonja E.; McDonagh, David L.; Venkatachalam, Aardhra M.; Premachandra, Lalith; Aiyagari, Venkatesh
Abstract : Supplemental digital content is available in the text. ABSTRACT: BACKGROUND: The Bispectral (BIS) monitor is a validated, noninvasive monitor placed over the forehead to titrate sedation in patients under general anesthesia in the operating room. In the neurocritical care unit, there is limited room on the forehead because of incisions, injuries, and other monitoring devices. This is a pilot study to determine whether a BIS nasal montage correlates to the standard frontal-temporal data in this patient population. METHODS: This prospective nonandomized pilot study enrolled 10 critically ill, intubated, and sedated adult patients admitted to the neurocritical care unit. Each patient had a BIS monitor placed over the standard frontal-temporal location and over the alternative nasal dorsum with simultaneous data collected for 24 hours. RESULTS: In the frontal-temporal location, the mean (SD) BIS score was 50.9 (15.0), average minimum BIS score was 47.0 (15.0), and average maximum BIS score was 58.4 (16.7). In the nasal dorsum location, the mean BIS score was 54.8 (21.6), average minimum BIS score was 52.8 (20.9), and average maximum BIS score was 58.0 (22.2). Baseline nonparametric tests showed nonsignificant P values for all variables except for Signal Quality Index. Generalized linear model analysis demonstrated significant differences between the 2 monitor locations ( P < .0001). CONCLUSION: The results of this pilot study do not support using a BIS nasal montage as an alternative for patients in the neurocritical care unit.